Therapist rotation: a novel approach for implementation of trauma-focused treatment in post-traumatic stress disorder. Issue 1 (1st January 2018) - Van Minnen, Agnes; Hendriks, Lotte; Kleine, Rianne De; Hendriks, Gert-Jan; Verhagen, Marije; De Jongh, Ad
ABSTRACT: Background : Trauma-focused treatments (TFTs) for patients with post-traumatic stress disorder (PTSD) are highly effective, yet underused by therapists.Objective : To describe a new way of implementing (adequate use of) TFTs, using a therapist rotation model in which one patient is treated by several therapists.Method : In this article, we will present two examples of working with therapist rotation teams in two treatment settings for TFT of PTSD patients. We explore the experiences with this model from both a therapist and a patient perspective.Results : Our findings were promising in that they suggested that this novel approach reduced the therapists' fear of providing TFT to PTSD patients, increased perceived readiness for TFT, and decreased avoidance behaviour within TFT sessions, possibly leading to better implementation of TFT. In addition, the therapeutic relationship as rated by patients was good, even by patients with insecure attachment styles.Conclusions : We suggest that therapist rotation is a promising novel approach to improve implementation of TFT for PTSD.